Improving Students’ Vocabulary Mastery through Word Chain Game (WCG) - Darma, Suci Dwina (LPPM Politeknik Raflesia, 2024)
This research aims to determine the extent of students' abilities in learning English, especially in terms of how much their vocabulary mastery increases. The subjects in this research were the first semester students of STIKES Al-Fatah Bengkulu for the 2023-2024 which consist of 20 students. This research was carried out as classroom action research which is implemented in 2 cycles using the Word Chain Games activities during the learning process. The research results show that the Word Chain Games method increases students' vocabulary mastery. Students also become become more active during the implementation of Word Chain Games activities which indicates that the activities are suitable in engaging students’ participation in English learning process, especially in vocabulary activities.